INIASI TUNAS SECARA KULTUR JARINGAN PADA STEVIA (Stevia rebaudiana Bertoni) DENGAN KOSENTRASI INDOLE BUTYRIC ACID (IBA) AND BENZYL AMINO PURINE (BAP) YANG BERBEDA - Anisa Hadiyana; Mohamad Ana Syabana; Susiyanti . (Jurnal Agroekoteknologi, 2015)
This research aims to know the initiation of bud stevia (Stevia rebaudiana Bertoni) in several concentrations of Indole Butyric Acid (IBA) and Benzyl Amino purine (BAP) are in in vitro. This research was conducted from August to October 2014 in engineering laboratory, Faculty of agriculture, University of Sultan Ageng Tirtayasa, Serang, Banten. This study used a Random group of Design with two factors. The first factor was the concentration of IBA 3 adequate for the applicable Io (0 mg/l), I1 (0.5 mg/l), I2 (1 mg/l) and the second factor is the concentration of BAP with 3 levels, apply B0 (0 mg/l), B1 (0.5 mg/l), B2 (1 mg/l). So, there are a total of 9 combination treatments repeated 3 times so that there are 27 units of the experiment. The results showed that treatment without IBA and BAP (I0B0) gave the best result in parameter first appearance of shoots (4 days after planting) and shoot length (0,85 cm). While, the treatment I2B2 (1 mg/l IBA and BAP) gave the best result in parameter leaves number (22 leaves).Keywords: initiation, stevia, growing regulatory substances, in vitro